Case Report: Kaposiform hemangioendothelioma with PIK3CA mutation successfully treated with sirolimus - Wang, Zuopeng; Yan, Hanlei; Ma, Yangyang; Yao, Wei; Zheng, Shan; Li, Kai (Frontiers in Oncology, 2023)
Kaposiform hemangioendothelioma (KHE) is an extremely rare, locally aggressive vascular neoplasm. The etiopathogenesis of KHE was still poorly understood. In the present study, we found a new mutation in KHE(c.685delA, p.Thr229fs).The patient of KHE with PIK3CA mutation showed complete regression with sirolimus treatment. We proposed the inclusion of KHE with PIK3CA mutation may correlate with good response to sirolimus.